Espelho, espelho meu, existe alguém mais belo ou saudável do que eu?: um estudo sobre o impacto da vaidade no awareness do consumidor de nutracêuticos - Cavalcante, Manoel Messias (2018)
What motivates the consumption of a product that is not a medicine, is not indicated for the treatment of any pathology, but that according to the industry's appeal contributes to the health and well-being of its consumers? What factors impact the consumption of this category? Nutraceuticals are functional foods that, because of their nutritional characteristics, provide health benefits beyond basic nutrition, or any substance considered as a food or part of the food with health benefits, whether in the prevention of some disease or in its treatment The main objective of this study was to evaluate the impact of the Vanity construct on consumer awareness of nutraceuticals. Secondarily, the age demographic variable was evaluated to identify any differences in the relationship between the main constructs. In order to obtain an answer to these questions, 214 questionnaires of a population of residents of Greater São Paulo and Grande Campinas of both sexes, aged 18 years and over, were evaluated through an online survey with a quantitative approach during the period of 20 from December 2017 to January 10, 2018. The study identified, with the use of exploratory techniques and the dichotomous logistic regression method, the confirmation of the relationship between Vanity and consumer awareness of nutraceuticals. The models presented significant results for the variable Vanity, with a P-value of 0.071, with the coefficient of determination (R2) of 7.73%. The second hypothesis with the Age variable had a supported result, with a P-value of 0.016 and an (R2) of 7.42%. The managerial implication of this study indicates a way to construct communication, marketing and relationship arguments that are closer to the real motivators of consumer buying, assisting the industry in its work of promoting, communicating, packaging and the relationship with consumers for the sustainable improvement of the sales performance of the products.